Efektifitas Penggunaan Aplikasi Platform Merdeka Mengajar dalam Meningkatkan Kompetensi Guru SMKN 1 Singingi Hilir - Agraini, T Rahmilia; Ummah, Adisty Akhoma; Waskito, Waskito; Yustisia, Henny (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
National education is rooted in religious and cultural values and is responsive to the demands of changing times. With changing times, teachers are required to be able to adapt to changes in the education system which is also developing. This research aims to evaluate the effectiveness of using the Merdeka Mengajar Platform in improving teacher competency. This research used a qualitative descriptive method with the research subjects being all teachers at SMKN 1 Singingi Hilir. Data was collected using instruments in the form of questionnaires distributed via Google Form. The results of this research show that the Merdeka Mengajar Platform has a significant impact on improving the competency and performance of teachers at SMKN 1 Singingi Hilir. Through features such as Self-Training and Teaching Tools, this platform helps teachers develop pedagogical, technological, and professional competencies.